Filologia polska oraz studia doktoranckie na kierunku porównawcza filologia słowiańska w latach 2003–2015 w Ołomuńcu - Sobotková, Marie (Postscriptum Polonistyczne, 2020)
The author presents the most important facts relating to the Polish Studies and Comparative Slavonic Philology doctoral studies offered by Palacký University in Olomouc. The author concentrates on the 2003–2015 period, describing the process of course restructuring, its current situation and students’ involvement.